Neuroprotective Properties of Erythropoietin in Cerebral Ischemia - Karagiannis, Asterios; Tziomalos, Konstantinos (Central Nervous System Agents in Medicinal Chemistry, 2006)
Since the human erythropoietin (EPO) gene was cloned in 1983, use of recombinant human EPO (rh-EPO) has become widespread for treating anemia in patients with end stage renal failure. Rh-EPO has a direct effect on haematopoiesis, reflected by increased hemoglobin levels. However, recent studies have shown that nerve cells also have erythropoietin receptors and that this cytokine is made in the nervous system and can function as a neuroprotective agent. In the last decade, it has been shown that EPO exerts general tissue protection including anti-apoptotic, antioxidant and angiogenesis effects. Perhaps best characterized is the mechanism whereby EPO inhibits apoptosis, with the effect believed to occur mostly by activation of the PI-3K-Akt axis or JAK2-STAT5 axis. This anti-apoptotic mechanism is not only important for erythropoiesis, but also appears to play an important role in other processes with high apoptotic activity, such as in stroke, retinal diseases and possibly chronic heart failure and myocardial infarction. Experimental studies in rats have shown that administration of EPO after six hours of arterial occlusion of the middle cerebral artery provided a 50% reduction in infarct size. Moreover, a recent phase 1-2 clinical trial has suggested that EPO can ameliorate neural damage in patients who have had a stroke. In this review, we discuss the neuroprotective properties and the future of rh- EPO therapy in patients with ischaemic stroke.
Keywords: Erythropoietin